Field efficacy of some insecticides against foliage feeding barley aphid (Rhopalosiphum maidis Fitch.) - Gupta, P.K.; Kumar, Jitendra; Khan, Javed Bahar; Singh, S.V.; Kanchan, Charul Kanchan (Journal of Cereal Research, 2019)
From economic cultivation point of view it is necessary to protect the crop from the attacks of barley aphid (Rhopalosiphum maidis) in early stages. The environmental factors play an important role in influencing the behaviour of this insect. It is main criteria for assessing the aphid infestation in the crop. The knowledge of appearance and its infestation period helps the growers to control the pest well in advance. To control the aphids through various chemicals/insecticides is other option. Many insecticides are available which can effectively control the aphid population and can reduce the damage to a large extent.On the basis of abovefacts, the present studies to evaluate the performance of different insecticides for the control of barley aphids was undertaken.